Nghiên cứu tổng hợp dung dịch ZnO pha tạp Al bằng phương pháp sol-gel ứng dụng chế tạo màng mỏng nhiệt điện AZO - Thông, Trịnh Quang; Doanh, Vũ Viết; Đăng, Lê Hải (Vietnam Journal of Chemistry, 2016)
This paper presents the study results of synthesis of ZnO solutions doped with Al at 1 % and 2 % weight concentration, based on Sol-Gel technique. Several experimental conditions and different solvents were applied to consider their influence on the sol-gel reaction. The multilayer AZO thin films were fabricated by dip-coating method using the solution prepared on Pyres glass substrates. The measurements of typical material properties to investigate the crystal structure information and film morphology were performed including of X-ray diffraction (XRD) and Field Effect Scanning Electron Microscope (FESEM). The average grain size of the samples were determined in the range of about 12-14 nm. The electrics properties were studied between room temperature and around 673 K. The film’s resistivity was measured by means of four-point probe to calculate the pretty electric conduction. The thermoelectric property is evaluated throughout the measurement of the Seebeck coefficients showing the relatively good values as desired. Both measurements were caried out in the temperature range of 27 oC (300 K) to 400 oC (673 K) in order to test the thermal withstanding of material. Keywords. Thin films, Al doped ZnO, Sol-Gel, XRD, SEM, Seebeck coefficient.